Michael Holroyd Smith papers - Smith, Michael Holroyd, 1847-1932.
Notebook containing Smith's 1879 lecture, "The Royal Road," concerning the possibility of mechanically powered flight; undated flier announcing a lecture by Smith, "Observations on Flight"; flier (November 23, 1908) advertising a lecture, "Mechanical Flight" by Herbert Chatley; and a business card with a formula explaining pelican flight written on the back of the card.
British mechanical engineer.
Collection material in English.
Keywords: Chatley, Herbert, -- 1885-1955.; Aeronautics; Flight; Pelicans -- Flight; Engineers